Polar Mesosphere Winter Echoes and their relation to infrasound - Belova, Evgenia; Kero, Johan; Näsholm, Sven Peter; Vorobeva, Ekaterina; Godin, Oleg A.; Barabash, Victoria (Luleå tekniska universitet, Rymdteknik, 2020)
Polar Mesosphere Winter Echoes (PMWE) are radar echoes that originate from the mesosphere at 50-80 km altitude and are observed with VHF radars during equinox and winter seasons. Strong PMWE are relatively rare phenomena, in most cases they are observed when the lower ionosphere displays high ionisation. Interpretations of observational results concerning PMWE are controversial and the origin of the echoes is still under debate. Especially intriguing is that in some cases of strong PMWE, the measured horizontal speeds of the radar reflecting structures can exceed 300 m/s. Radar reflection (scattering) by infrasound waves at frequencies below about 2 Hz was suggested in order to explain these observations. We will give recent examples of PMWE events of high horizontal speed as observed with the 52 MHz MST radar (ESRAD) located at Esrange (68°N, 21ºE) in northern Sweden. Together with this we will analyse infrasound measurements made at ground-based stations near Kiruna (67.5°N, 20.13ºE) and at the infrasound station IS37 (69°N, 18ºE) in Norway during these events. We discuss prospective relations between PMWE and the microbaroms that are generated by ocean swell in the North Atlantic.